Fundamentals of solid-state lighting : LEDs, OLEDs, and their applications in illumination and displays - Vinod kumar khanna
"This book presents an up-to-date, comprehensive survey of the principles, technology, and applications of solid-state devices for lighting and displays. Compared to traditional electrical filaments, arc lamps, and fluorescent lamps, solid-state lighting offers higher efficiency, reliability, and environmentally friendly technology. The book covers a range of solid-state devices, technologies, and materials used for lighting and displays. It also examines auxiliary but critical requirements of efficient applications, such as modeling, thermal management, reliability, and smart lighting. "--